2008
DOI: 10.1177/0093854808326525
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Recidivism by Mentally Disordered Offenders Using the LSI-R:SV

Abstract: The Level of Service Inventory—Revised: Screening Version (LSI-R:SV) has proven to validly predict reoffending in general offender populations but has not previously been studied specifically with offenders who have a major mental illness, including those with a dual diagnosis. This research project measures the validity of the LSI-R:SV for use with 208 mentally ill offenders who were released from a secure forensic hospital in Melbourne, Australia. Results indicate that the LSI-R:SV is a good predictor of rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 23 publications
(46 reference statements)
0
32
1
3
Order By: Relevance
“…Only when combined with co-morbid substance abuse, was severe mental illness significantly related to a higher incidence of violence. Additional lines of research have confirmed the moderating effect of SUD coupled with mental illness among adult samples (Ferguson, Ogloff, & Thomson, 2009;Ogloff et al, 2004;Rezansoff et al, 2013;Steadman et al, 1998;Wallace, Mullen, & Burgess, 2004). Alternatively, a few studies have found a significant relationship between mental illness and the likelihood of violence, irrespective of substance abuse (Short, Thomas, Mullen, & Ogloff, 2013;Van Dorn, Volavka, & Johnson, 2012).…”
Section: Mental Health Concerns and Criminal Behaviormentioning
confidence: 95%
See 1 more Smart Citation
“…Only when combined with co-morbid substance abuse, was severe mental illness significantly related to a higher incidence of violence. Additional lines of research have confirmed the moderating effect of SUD coupled with mental illness among adult samples (Ferguson, Ogloff, & Thomson, 2009;Ogloff et al, 2004;Rezansoff et al, 2013;Steadman et al, 1998;Wallace, Mullen, & Burgess, 2004). Alternatively, a few studies have found a significant relationship between mental illness and the likelihood of violence, irrespective of substance abuse (Short, Thomas, Mullen, & Ogloff, 2013;Van Dorn, Volavka, & Johnson, 2012).…”
Section: Mental Health Concerns and Criminal Behaviormentioning
confidence: 95%
“…(The lone exception was personality pathology and psychopathy, both of which had robust associations with general and violent recidivism.) Among the very few studies, however, that examined the predictive validity of LS risk measures among dually diagnosed adult patients, Ferguson et al (2009) found that the LSI-R:SV did not significantly predict any recidivism outcomes (AUC values ranged from .50 to .51). The relationship of mental disorder and dual diagnosis with criminogenic needs has yet to be examined in young offender populations and thus will be a focus of the present study.…”
Section: Mental Health Concerns and Criminal Behaviormentioning
confidence: 99%
“…Drug offenders are among the groups mentioned as difficult to assess (Andrews & Bonta, 2010). Different risk assessment measures have been validated for some groups including mentally disordered offenders (Ferguson, Ogloff, & Thompson, 2009), male batterers (Hendricks, Werner, Shipway, & Turinetti, 2006), adult and juvenile sex offenders (Prentky & Righthand, 2003; Vrana & Sroga, 2008) and adult drug offenders (Kelly & Welsh, 2008). However, no corresponding validations have been conducted among juvenile drug offenders.…”
Section: Assessing Risk For Different “Types” Of Offendersmentioning
confidence: 99%
“…The forensic psychiatric inpatient population has been shown to have alarmingly high rates of substance use histories (Ferguson, Ogloff, & Thomson, 2009;Kaur, Daffern, & Thomas, 2009;Mueser, et al, 2000;Ogloff, Lemphers, & Dwyer, 2004;Scott, Whyte, Burnett, Hawley, & Maden, 2004). In the UK, the rate of substance use in the inpatient population is twice the rate observed in the general population .…”
Section: Introductionmentioning
confidence: 99%